Nursing and mHealth - Catherine Samples; Zhao Ni; Ryan J. Shaw (International Journal of Nursing Sciences, 2014)
Innovations in mobile health (mHealth) technology offer applications to promote wellness management and health behavior change outside of formal clinical settings. Nurses can help to move mHealth into mainstream health care by understanding its potential to change the landscape of health intervention delivery, incorporating mHealth into patients' day to day preventive care strategies, and supporting the science of mHealth's effectiveness.